2015
DOI: 10.1159/000442446
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Risk in Chronic Obstructive Pulmonary Disease: The Effects of Drug Class and Inclusion Criteria

Abstract: Background: This study analyzed the risk of clinical trial failure in chronic obstructive pulmonary disease (COPD) drug development between 1998 and 2015. We investigated elements that influenced clinical trial risk and factors that could improve outcomes during development. Objectives: This study aims to quantify clinical trial risk for drug development in COPD and factors that affect clinical trial risk. Methods: Drugs that commenced their phase I testing in this indication from 1998 onwards were retrieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This study has several limitations, some of which have been previously described in other research studies of similar methodology 8–13 . The databases used were extensive but not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several limitations, some of which have been previously described in other research studies of similar methodology 8–13 . The databases used were extensive but not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study methodology has been described and used to analyze drug development in other disease areas 8–13 . The phase I, II, and III clinical trials for the treatment of ALL, CLL, AML, and CML were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, studies examining a maintenance treatment for COPD enroll patients with moderate to very severe states of the disease, as GOLD group A patients with COPD are usually considered adequately managed with short‐acting β2‐adrenoreceptor agonist or short‐acting muscarinic antagonist as needed. Furthermore, a review of COPD phase I−III clinical studies conducted between 1998 and 2015 found a 22% greater success rate when studies included patients with GOLD 3 or 4 stages, vs. GOLD 1 or 2 stages . Currently, there is a gap in knowledge regarding how early treatment with dual bronchodilator therapy should start and clinical studies to determine whether optimizing lung function in those with the mildest COPD can alter disease progression are needed.…”
Section: Study Design Considerationsmentioning
confidence: 99%